Strategi Personal Branding Akun @banjarnyaman pada Platform Tiktok sebagai Media Promosi Kuliner Lokal - Rahmadini, Nasifa Noor; Hidayah, Sri (Prodi Sosiologi FISIP ULM, 2026)
The rise of culinary content on social media has led food influencers to go beyond merely showcasing food visuals, they also craft personal identities to earn audience trust and engagement. This study aims to describe and analyze how the Tiktok account @banjarnyaman builds its branding as a food influencer through various communicative elements such as language style, visuals, voice-over, and distinctive slogans or jargon. The research uses a descriptive qualitative approach with both primary and secondary data sources, conducted in Banjarmasin City, focusing primarily on Tiktok as a digital platform. Data collection techniques include participatory observation, in-depth interviews, and documentation, analyzed using the Miles and Huberman model. The findings reveal that @banjarnyaman successfully constructs a strong and consistent self-image through expressive voice-overs, a mix of Banjar and casual language, and a unique slogan, “Endol Takendol Kendol,” that fosters emotional closeness with the audience. The personal branding displayed is a communicative process shaped by local preferences and digital habits. The audience responds positively and feels emotionally connected, while MSMEs perceive the account as a credible promotional platform. These findings are analyzed using Eriyanto’s branding theory and Stuart Hall’s encoding/decoding theory to understand the formation of self-image and the meanings interpreted by the audience. Future research is suggested to explore other food influencers’ strategies in building cross-segment audience connections and to examine the broader impact on consumption patterns in society.